Experimental models used in evaluating anti-tuberculosis vaccines: the latest advances in the field - Alejandra Mantilla Galindo; Marisol Ocampo; Manuel Alfonso Patarroyo (Taylor & Francis Group, 2019)
Introduction: Tuberculosis is an infectious disease which is caused by bacilli from the M. tuberculosis complex. The Mycobacterium bovis Bacillus Calmette-Guérin vaccine is currently available as a prophylactic tool for preventing the disease; it has been shown to be efficient in preventing disseminated forms of tuberculosis during early ages; however, its efficiency is limited in areas where individuals have had prior exposure to environmental mycobacteria, and its efficacy decreases with a host's age. Areas covered: Following a comprehensive search of the available literature, this review describes some of the most frequently used animal models, the most frequently used methods for evaluating efficacy in animal models and some in vitro strategies as alternatives for evaluating vaccines. Expert opinion: Identifying the animal models used up to now for evaluating vaccines during their development stages, their characteristics and limitations, as well as knowledge regarding strategies for evaluating promising vaccine candidate efficacy, will ensure more efficient, reliable and reproducible pre-clinical trials. Although much of the knowledge accrued to date concerning vaccine effectiveness against tuberculosis has been based on animal models, it is clear that large questions still need to be resolved and that extrapolation of such efficacy to humans has yet to be achieved.